Jack Kerouac, King of the Beats: a Portrait - Miles, Barry -1943 (London Virgin, 2002)
Barry Miles, friend and official biographer of Allen Ginsberg and William Burroughs, presents a provocative and intimate portrait of one of the 20th century's most influential writers. Meticulously researched, this is a compelling exploration of the complex man and extraordinary writer whose creative mishmash of joyous incoherence, drug-induced ecstasy, genuine mysticism, and constant craving has persuaded so many to take to the road. In conformist 1950s America, Jack Kerouac's On the Road was greeted with both delirium and dismay. For his generation, he and the universe he created symbolized freedom. He identified the living pulse of America in jazz clubs and fast cars, and found vibrancy in hobos hopping freight cars and traveling the highways. In his hunt for the big experience and his longing for greatness, Kerouac has inspired each successive generation. He is now an icon, an image, an attitude, forever personifying "the mad ones, the ones who are mad to live, mad to be saved, desirous of everything at the same time." This candid biography reveals a man full of contradictions, rarely at peace with himself.
Includes bibliographical references (p. 317-323) and index.
Keywords: Kerouac, Jack -- 1922-1969; Poetry; Literature; Biography; Cuckoo